Association between IL12B polymorphisms and inflammatory bowel disease in Caucasian population: A meta-analysis. (December 2020) - Wu, Peng-bo; Wu, Xiao-man; Qian, Rao; Hong, Chai; Yitian, Guo; Zhang, Guo; Yu, Yuan-jie
Abstract: Background: Published studies on association between IL12B ( G/A ) rs10045431, ( T/C ) rs68876 95 polymorphisms and inflammatory bowel disease (IBD) risk in Caucasian population have yielded conflicting results. The aim of this study was to potentially provide more reliable conclusions by conducting a meta-analysis. Methods: Published studies concerned association between IL12B rs10045431, rs6887695 polymorphisms and IBD were searched from the Wiley Online Library, PubMed, Web of Science and the CNKI database. The odds ratio (OR) with 95% confidence interval (CI) was calculated to evaluate the strength of the relationship. The false positive report probabilities (FPRPs) test and trial sequential analysis (TSA) was performed to investigated the reliability of results. Results: A total of 20 studies comprising 10761 Crohn's disease (CD), 10921 ulcerative colitis (UC) and 18381 controls were included in this meta-analysis. Overall, the pooled results showed that IL12B rs6887695 polymorphism significantly increased both CD and UC risk under all model, while IL12B rs10045431 polymorphism dramatically decreased both CD and UC risk under all model. FPRP and TSA demonstrated that above associations was confirmed in the present study. Conclusion: The results of meta-analysis indicate IL12B rs10045431 and rs6887695 polymorphisms significantly associate with IBD in Caucasian population.